Peran Promosi Melalui Iklan Katalog dalam Keputusan Pembelian Konsumen (Studi Kasus Pada Minimarket Indomaret di Kota Bengkalis) - Afis Afis; Tri Handayani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2020)
In this digital era, there are so many online promotion strategies that can be developed by business people, so that offline promotion is felt, one of which is by using a log as the second alternative in business. This study aims to determine the effect of promotion through catalog advertising on purchasing decisions with a case study at the Indomaret Minimarket in Bengkalis City. The problem in this research is how the effect of catalog advertising on purchasing decisions made by consumers and how much influence it has. The subjects in this study were consumers of the Indomaret Minimarket by taking information from 100 respondents using a questionnaire instrument that was sourced from the development of research instruments. The technique of collecting samples was purposive sampling and then the results of the information were analyzed using correlation and regression analysis. The results showed that there was a significant correlation and effect of promotion with catalog advertising on consumer purchasing decisions, namely 42.1%. This shows that the catalog promotion strategy has an impact in achieve target consumers for a business.